Superior 125-month outcome through cetuximab in the larynx organ preservation trial DeLOS-II: a single study center’s experience - Wichmann, Gunnar; Wald, Theresa; Zebralla, Veit; Stoehr, Matthaeus; Pirlich, Markus; Wiegand, Susanne; Kunz, Viktor; Dietz, Andreas (Frontiers in Oncology, 2024)
IntroductionThe larynx organ preservation (LOP) trial DeLOS-II enrolled n = 173 patients with advanced laryngeal/hypopharyngeal squamous cell carcinoma (LHSCC) amenable (only curatively resectable) through total laryngectomy (TL) to receive induction chemotherapy (IC) with TPF [docetaxel (T), cisplatin (P), and 5-fluorouracil (F)] (arm A, 85 patients) or additional cetuximab (E) weekly (arm B, 88 patients). Responders with endoscopic estimated tumor surface shrinkage (ETSS) ≥30% after 1 cycle IC (IC-1) received a further two cycles of IC followed by radiotherapy (RT), whereas TL was recommended for non-responders. Arm B failed to show superior 24-month laryngectomy-free survival (LFS) and overall survival (OS), the protocol-specified primary and secondary endpoints. Ten years after the last per-protocol visit, we are interested in the long-term outcome of our clinic’s DeLOS-II patients.MethodsOur cohort of 52 DeLOS-II patients accrued between 2007 and 2012 included 27 and 25 patients randomized to arms A and B, respectively. F was omitted because of severe toxicity with amendment 2 of the DeLOS-II protocol, leading to 21 and 31 patients receiving TPF and TP IC backbone, respectively. Follow-up data were collected using electronic health records and information from the German Centre for Cancer Registry Data to evaluate long-term LFS and OS in treatment groups.ResultsAccording to ETSS ≥ 30%, 42 patients (80.8%; 21 and 21 corresponding to 77.8% and 84.0% in arms A and B, respectively) were responders to IC-1 and underwent the LOP attempt. Recommending early TL to non-responders (ETSS < 30%), eight patients (five and three in A and B, respectively) underwent early TL. At 125 months, 22 (eight and 14) patients were alive: 17 (six and 11) with a functioning larynx and five (two and three) without a larynx. Arm B had superior OS (p = 0.023). Disease-specific survival (DSS) and tumor-specific survival were not different, whereas non-cancer-related survival (NCRS) was impaired in arm A (p = 0.018). Receiving TP or TPF IC did not significantly influence survival. Pairwise comparing OS of patients receiving TP, TPF, TPE, and TPFE revealed a benefit from cetuximab in TPE vs. TP (p = 0.020).ConclusionWhile the per-protocol DeLOS-II results earlier reported comparable 24-month LFS and OS in arms A and B, our subcohort’s long-term follow-up data demonstrate a superior 125-month outcome in arm B.